Hubungan Motivasi Belajar Dengan Adversity ‎Quotient (AQ) Siswa Pada Mata Pelajaran ‎Matematika Kelas X SMKN 1 AMPEK ANGKEK Tahun ‎Pelajaran 2021/ 2022‎ - Yela Marlina; Haida Fitri (Journal on Education, 2023)
This research is motivated by the large number of students who have an adversity quotient in mathematics which tends to be less good. It can be seen from students who are less enthusiastic and less enthusiastic in learning and students who show a pessimistic attitude when they encounter difficulties or problems in learning mathematics and have not been able to find solutions how to solve these problems. This is thought to be caused by poor student motivation. Based on these conditions, the formulation of the problem in this research is whether there is a relationship between learning motivation and students' adversity quotient (AQ) in class X mathematics at SMKN 1 Ampek Angkek for the 2021/2022 academic year. The hypothesis in this study is "There is a significant relationship between learning motivation and students' adversity quotient (AQ) in class X mathematics at SMKN 1 Ampek ‎Angkek for the 2021/2022 academic year."‎ This type of research is correlational research with quantitative methods. The population in this study were all class X students of SMKN 1 Ampek Angkek, totaling 277 students. And the sample in this study were 34 students taken randomly. The research instruments contained a learning motivation questionnaire and an Adversity Quotient questionnaire The results of this study obtained Z0 = 3.412 and Z_(a/2) = 1.96, at the real level α = 0.05. This shows that Z0 ≥ Z_(a/2) so that it can be concluded that H0 is rejected and H1 is accepted, which means that there is a significant relationship between learning motivation and students' adversity quotient (AQ) in mathematics class X at SMKN 1 Ampek Angkek in the 2021 academic year. /2022‎.